2007
DOI: 10.1074/jbc.m707127200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Regulation of N-Acetylglutamate Kinase by PII in Arabidopsis thaliana

Abstract: PII is a highly conserved regulatory protein found in organisms across the three domains of life. In cyanobacteria and plants, PII relieves the feedback inhibition of the rate-limiting step in arginine biosynthesis catalyzed by N-acetylglutamate kinase (NAGK). To understand the molecular structural basis of enzyme regulation by PII, we have determined a 2.5-Å resolution crystal structure of a complex formed between two homotrimers of PII and a single hexamer of NAGK from Arabidopsis thaliana bound to the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 38 publications
(51 reference statements)
6
85
0
Order By: Relevance
“…It has been shown that 2-OG controls P II target interactions that involve the T loop, with X-ray structural information available for the S. elongatus and A. thaliana P II -NAGK complex (22,23), the S. elongatus P II -PipX complex (27), and the E. coli GlnK-AmtB complex (28,29). The mechanism of 2-OGmediated P II -target control was clarified here with the cognate P II -NAGK complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that 2-OG controls P II target interactions that involve the T loop, with X-ray structural information available for the S. elongatus and A. thaliana P II -NAGK complex (22,23), the S. elongatus P II -PipX complex (27), and the E. coli GlnK-AmtB complex (28,29). The mechanism of 2-OGmediated P II -target control was clarified here with the cognate P II -NAGK complex.…”
Section: Discussionmentioning
confidence: 99%
“…The ATP molecule observed in the S2 site is significantly distorted relative to that in S1 and S3. ADP could involve additional residues, possibly from its prolonged C-terminal segment, which contacts the effector moleculebinding site (22). The fact that all residues revealed here to be involved in 2-OG binding are highly conserved among P II proteins (see also Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The C-terminal residues extend out from the b4 strand to form a C-loop (Asp97 to Leu112) and has a 3 10 helix embedded within it between Gly108 and Ala111, consistent with other PII like protein structures. 16,24,[30][31][32][33][34][35] Structure of the ATP bound Mtb PII protein…”
Section: Structure Of the Mtb Apo Pii Proteinmentioning
confidence: 99%